The Implementation of Integrated STEM Skills with Learning Tools in Indonesian Secondary Schools - Setyaningsih, Endang; Agustina, Putri; Anif, Sofyan; Ahmad, Che Nidzam Che; Khoirussyihab, Naufal; Oktavia, Princes Orinta; Sofyan, Iyan; Saputra, Alanindra; Adnan, Mazlini (Universitas Muhammadiyah Surakarta, 2025)
In the era of the Fourth Industrial Revolution, it is essential to develop competitive individuals equipped with Science, Technology, Engineering, and Mathematics (STEM) competencies. The government, actively promotes the integration of STEM across all educational levels, including secondary schools. This emphasis arises because STEM competencies are critical for the Fourth Industrial Revolution and help individuals address real-world challenges. This literature review explores the implementation of STEM in Indonesia, focusing on the tools and strategies applied in secondary education. Over the past six years (2016–2021), changes in STEM practices have been identified. From 25 articles were analyzed, covering aspects such as instructional materials and pedagogical strategies in secondary schools. The findings reveal the distribution of resources as follows: curriculum score 7.69%, lesson plans 20.51%, modules 15.38%, student worksheets 33.33%, books 10.25%, exam questions 10.25%, and curriculum documents 2.56%. In terms of teaching approaches, the data show 4% engagement in discovery-based learning, 52% in project-based learning, 36% in problem-based learning, and 4% in scientific learning. Overall, the results indicate that STEM competencies are still not widely implemented in Indonesia, as most scores remain at or below 50%. Thus, further efforts are necessary to strengthen STEM integration in the country.